2003
DOI: 10.1046/j.1365-2133.2003.05439.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced skin thickness: a new minor diagnostic criterion for the classical and hypermobility types of Ehlers-Danlos syndrome

Abstract: We propose that the reduced thickness of the dermis as determined by high-resolution 20-MHz ultrasound can be used as a new minor criterion in the diagnosis of the classical and the hypermobility types of EDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…The diagnosis is based on clinical features; in fact, there are no pathognomonic laboratory tests and no specific pathologic features in most types. The diagnosis is full fit by the presence of one of three major criteria (skin hyperextensibility, tissue fragility, and joint hypermobility), while the presence of one or more minor criteria (recurrent joint dislocations, chronic limb or joint pain, positive family history of EDS, hypermobility type, easy bruising, functional bowel disorders as functional gastritis, irritable bowel syndrome, neurally mediated hypotension or postural orthostatic tachycardia) [4] is necessary to distinguish a specific type of EDS [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis is based on clinical features; in fact, there are no pathognomonic laboratory tests and no specific pathologic features in most types. The diagnosis is full fit by the presence of one of three major criteria (skin hyperextensibility, tissue fragility, and joint hypermobility), while the presence of one or more minor criteria (recurrent joint dislocations, chronic limb or joint pain, positive family history of EDS, hypermobility type, easy bruising, functional bowel disorders as functional gastritis, irritable bowel syndrome, neurally mediated hypotension or postural orthostatic tachycardia) [4] is necessary to distinguish a specific type of EDS [2].…”
Section: Discussionmentioning
confidence: 99%
“…The major criteria of diagnosis are the skin laxity, velvet skin, and the joint hypermobility; the minor ones are recurrent joint dislocations and chronic limb or joint pain. [2,3] It has been considered for long time a mild form of EDS, but this conception is not correct because it is the more invalid one for the muscular impairment, and in some patients, it has been described vascular and cardiac disfunction, including mitral valve prolapse, aortic dilatation, and aortic dissection/rupture [4].…”
Section: Introductionmentioning
confidence: 99%
“…A few histologic studies have been reported, 5,12,13 but they are invasive. High-resolution ultrasound imaging has been used for longer than 20 years in dermatology 14 to analyze and quantify dermal changes in many conditions such as diagnosis and delimitation of tumors, 15 follow-up of inflammatory diseases, 16 diagnosis of collagenous diseases, 17 and evaluation of edema. 18 This imaging tool allows accurate measurement of dermal thickness.…”
mentioning
confidence: 99%
“…The diagnosis is based on clinical features; in fact, there are no pathognomonic laboratory tests and no specific pathologic features in most types (4). The diagnosis is full fit by the presence of one of three major criteria (skin hyperextensibility, tissue fragility, and joint hypermobility), while the presence of one or more minor criteria (smooth, velvety skin, subcutaneous spheroids, recurrent joint dislocations or subluxations, chronic limb or joint pain, positive family history of EDS, muscle hypotonia, easy bruising, functional bowel disorders, [functional gastritis and/or irritable bowel syndrome], high, narrow palate, dental crowding, and neurally-mediated hypotension or postural orthostatic tachycardia) is necessary to distinguish a specific type of EDS (4,11,12). To our knowledge, extensive cerebral calcification in EDS patients has not been previously reported in the medical literature.…”
Section: Introductionmentioning
confidence: 99%